C# .net web developer's guide - Turtschi, Adrian (Rockland, Mass. : Syngress, 2002)
Microsoft's C# ("C sharp") is a modern, object-oriented programming language built from the ground up to exploit the power of XML-based Web services on Microsoft's new .NET platform. With its Visual C++ development system heritage, C# will enable millions of C and C++ developers to use existing skills to rapidly build sophisticated XML-based .NET applications. Why Will Web Developers Switch to C#? ... Because it's the ideal solution for C and C++ programmers who need to combine rapid development with the power to access all the functionality of the Microsoft.NET platform. They want an environment that is completely in sync with emerging Web standards and one that provides easy integration with existing applications. C#.net Web Developer's Guide will enhance developer productivity and help them eliminate programming errors that can lead to increased development costs. This book teaches Web developers to quickly and easily build solutions for the Microsoft .NET platform. Web developers will learn to use C# components to build Web services and applications that are available across the Internet, from any application running on any platform. * Timely coverage of newly released product - programmers and developers are anxious to learn about the new technology * Comes with Syngress' revolutionary wallet-sized CD containing a printable HTML version of the book and all of the source code examples and demos of popular C# upgrade and programming tools.
Includes index.
"Develop and deliver enterprise-critical desktop and web applications with C#.net"--Cover.
Keywords: C# (Computer program language).; Microsoft .NET Framework; Programming languages (Electronic computers).; Electronic books